IDENTIFYING HEALTHCARE WORKERS' INTENTION TOWARD TELEHEALTH IN INDONESIA DUE TO COVID-19 PANDEMIC - Muhammad Rafi Fathurahman; Mursyid Hasan Basri; Prawira Fajarindra Belgiawan (Universitas Airlangga, 2022)
Background: Healthcare sectors adopted various steps during the Covid-19 pandemic to prevent virus transmission, including limiting patient numbers. Telehealth can be an alternative solution since healthcare institutions can provide services without direct contact. Aims: This research aims to analyze healthcare workers' intentions in Indonesia toward telehealth using the unified theory of acceptance and use of technology (UTAUT) framework with additional variables. Methods: A literature review was undertaken to develop a framework tested using Partial Least Square-Structural Equation Modeling (PLS-SEM). This study was conducted with Indonesian healthcare institutions in Bandung and Surakarta. Participants consisted of doctors and nurses. Results: Of 200 participants, this finding showed effort expectancy, social influence, facilitating conditions, self-efficacy, and technology anxiety influenced the intention to adopt telehealth (p-Value ≤ 0.05). However, performance expectancy and perceived security and data have no significant influence (p-Value > 0.05). This study discovered that performance expectancy is influenced by effort expectancy (β = 0.727), while effort expectancy is influenced by self-efficacy (β = 0.642). Conclusion: Indonesian healthcare institutions must be concerned with factors affecting telehealth implementation, especially with data security, which has proven insignificant. Further research is required to optimize the application.